Apocalyptic Thinking after 9/11: An Interview with René Girard - Girard, René (Substance, 2008)
An interview with René Girard on the effects of the 9/11 terrorist attack is presented. When asked about how he sees the events of 9/11 in retrospect, Girard comments that people in the U.S. seems to have forgotten and deemphasized the event because of the war in Iraq. Girard sees 9/11 as a seminal event, a mere continuation and a new dimension of the violence in the 20th century. He believes that the threat of terrorism goes beyond politics since there is a religious aspect.